International Labour Organisation report on the organisation and administration of the national provident fund - International Labour Organisation (Lagos : Federal Ministry of Information, 1972)
The federal government of the Republic of Nigeria requested the services of an expert from the International Labour Organisation to review the working of the national provident fund.
nmn, 17/04/19
Ref.
Keywords: International Labour Organisation; National provident fund; Report - national provident fund; National provident fund - administration